Enantioselective formal total synthesis of (-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Organic Letters, 2019)
The enantioselective formal total synthesis of (-)-quinagolide has been accomplished in a linear sequence of 8 purification steps from pyridine. The key steps are (a) organocatalyzed Diets-Alder reaction for fixing all three stereocenters on piperidine ring; (b) protecting group enabled deoxygenation of isoquinuclidine skeleton under Birch reduction condition; (c) Lewis acid (TiCl4) catalyzed intramolecular Friedel-Crafts cyclization of dicarboxylic acid; and (d) one-pot diastereoselective ketone reduction-intramolecular cyclization to form oxazolidinone which enables trans-geometry installation. During the course of the synthesis, an interesting reductive cleavage of the C-N bond in the electron-deficient isoquinuclidine skeleton under the Birch reduction conditions has been observed. This is the first synthetic effort to access the core skeleton of (-)-quinagolide.